Pulmonary Embolism: An observational study at Narayana Hrudayalaya Institute of Cardiac Sciences, Bangalore, India - Das, PK; Rahman, F; Shetty, PK; Shetty, DP (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):399-404 The abstract of this article is available on the PubMed website